PENGARUH KOMPENSASI DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION DI OKUI KOPI - Muhammad Angga Praditya; Sulastri Irbayuni (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Business movements in the food and beverage sector in Indonesia are increasingly dynamic, especially coffee drinks which are in demand by the public. Currently, coffee shops in Indonesia have changed their function, apart from meeting coffee needs, they can also function as a place to socialize, expand networks, and even work. This study aims to: (1) determine the effect of compensation on turnover intention of workers at OKUI Kopi; (2) know the effect of work-life balance on turnover intention of OKUI Kopi workers; This analysis uses independent variables, namely compensation and work-life balance. The dependent variable is turnover intention. The data used in this study is primary data in the form of filling out questionnaires via google form and interviews via teleconference. Secondary data in the form of data collection through journals, books, and previous writing. Data analysis tested the validity and reliability of the questionnaire data with correlation coefficients using SPSS 20.0 software. The analysis technique uses Partial Least Square (PLS), hypothesis testing assumptions on PLS related to structural equation modeling. The results of this study show that high compensation can lead to low turnover intention, the lower the salary, the higher the turnover intention that occurs at OKUI Kopi. A high work-life balance can increase the occurrence of turnover intention, so the lower the time to do hobbies, the higher the turnover intention that occurs at OKUI Kopi.